Sport specialization in middle school and high school long-distance runners - Garcia, M. C.; Taylor-Haas, J. A.; Rauh, M. J.; Toland, M. D.; Bazett-Jones, D. M. (Journal of Athletic Training, 2021)
Context: Previous reports suggested that highly specialized adolescent athletes may be at a higher risk of injury, worse sleep quality, and less sport enjoyment than low-level specialized athletes. To date, the sport specialization literature has primarily addressed adolescent athletes in a variety of sports. However, whether the findings on sport specialization in predominantly nonrunning athletes are generalizable to adolescent long-distance runners is unknown. Objective: To compare injury history, running volume, quality of life, sleep habits, and running enjoyment among male and female middle school and high school long-distance runners at different sport specialization levels. Design: Cross-sectional study. Setting: Online survey. Patients or Other Participants: A total of 102 male (age = 15.8 ± 0.9 years) and 156 female (age = 15.6 ± 1.4 years) uninjured middle school and high school athletes who participated in long-distance running activities (completion rate = 50.7%). Main Outcome Measure(s): Participants were stratified by sex and sport specialization level (low, moderate, or high). Group differences were assessed in self-reported running-related injuries, running habits, EQ-5D-Y quality of life, Pittsburgh Sleep Quality Index sleep quality, sleep duration, and running enjoyment. Results: Highly specialized male and female middle school and high school long-distance runners reported more months of competition per year (P < .001), higher weekly run distance (P < .001), more runs per week (P < .001), higher average distance per run (P < .001), and greater running enjoyment (P < .001) than low-level specialized runners. Adolescent boys reported a higher average weekly run distance (P = .01), higher average distance per run (P = .01), and better sleep quality (P = .01) than adolescent girls. No differences among sport specialization levels were found for running-related injuries (P = .25), quality of life (P = .07), sleep quality (P = .19), or sleep duration (P = .11) among male or female middle school and high school runners. Conclusions: Highly specialized male and female middle school and high school long-distance runners reported higher running volumes and running enjoyment than low-level specialized runners. However, high-level specialized runners did not describe a greater number of running-related injuries, lower quality of life, or lower sleep quality or duration as expected.